2018
DOI: 10.1155/2018/2910198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Contribution of Nocardia spp. and Mycobacterium tuberculosis to Pulmonary Infections among HIV and Non-HIV Patients at the Komfo Anokye Teaching Hospital, Ghana

Abstract: Tuberculosis (TB) is a major cause of human mortality particularly in association with the human immunodeficiency virus (HIV). Nocardia spp. has emerged as an opportunistic infection especially in HIV patients. The high prevalence of TB and HIV coupled with the lack of a definitive laboratory diagnosis for Nocardia spp. could lead to misdiagnosed pulmonary TB. This study determined the prevalence of pulmonary infections due to Nocardia spp. and Mycobacterium tuberculosis in sputum of HIV and non-HIV patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…While former reports showed that males comprised more than half the patients with nocardiosis 1,[27][28][29] , males comprised only 48% of our patients with nocardiosis. We found no significant difference in the distribution of sex between the groups.…”
Section: Discussioncontrasting
confidence: 51%
“…While former reports showed that males comprised more than half the patients with nocardiosis 1,[27][28][29] , males comprised only 48% of our patients with nocardiosis. We found no significant difference in the distribution of sex between the groups.…”
Section: Discussioncontrasting
confidence: 51%
“…Ninan et al [32], 2016 South India 131 cases: N. asteroides (73), Nocardia spp. (32), N. brasiliensis (2), aerobic actinomycetes (24) Skin (36), eye (36), pulmonary (35), immunosuppressive therapy (48) Nampoory et al [47], 1996 Kuwait 6 cases: N. asteroides (4), N. otitidiscaviarum (1), N. farcinica (1) Pulmonary nocardiosis (3: with 2 cerebral abscess, 1 meningitis); perinephric abscess (1), thigh abscess (1), ischiorectal abscess (1) Lai et al [65], 2011 Taiwan 138 isolates: N. brasiliensis (58), N. cyriacigeorgica (22), N. farcinica (11), N. beijingensis (8), N. otitidiscaviarum (7), N. nova (6), N. puris (6), N. asiatica (5), N. flavorosea (5), N. abscessus (3), others 7Skin and soft-tissue, respiratory tract specimens, brain biopsy, blood, lymph node…”
Section: Casesmentioning
confidence: 99%
“…Nocardiosis in HIV-positive patients is reported to occur in 3.4-16.7% of cases in various centers [22][23][24]. The course of the disease may be localized or disseminated; in a Spanish study on HIV and nocardia coinfection, 44% of cases had disseminated nocardiosis [25].…”
Section: Nocardiosis: a Global Problemmentioning
confidence: 99%
“…Concomitant infections in immunocompromised individuals are common and can include Nocardia co-infecting with other bacterial, fungal, and viral pathogens [11,12]. Tuberculosis (TB) caused by another actinomycete, Mycobacterium tuberculosis, is associated with chronic lung disease, and owing to the similarity in diagnosis and clinical manifestation of nocardiosis and TB, accurate identification of these two acid-fast bacilli can be difficult [13][14][15]. In some cases, concomitant nocardial and TB infections have also been observed and are more likely to occur in HIV-infected individuals [16].…”
Section: Nocardia Infections: Difficult To Identify and Difficult To mentioning
confidence: 99%
“…In some cases, concomitant nocardial and TB infections have also been observed and are more likely to occur in HIV-infected individuals [16]. Treatment of choice for tuberculosis is ineffective for nocardiosis, underscoring the importance of accurate diagnosis for effective treatment [13,14,17].…”
Section: Nocardia Infections: Difficult To Identify and Difficult To mentioning
confidence: 99%